Costing alternative transfer modalities - Margolies, Amy; Hoddinott, John F. (International Food Policy Research Institute, 2014)
Discussions regarding the merits of cash and food transfers by academics and implementers alike focus on their relative impacts. Much less is known about their relative costs. We apply activity-based costing methods to interventions situated in Ecuador, Niger, Uganda, and Yemen, finding that the per transfer cost of providing cash is always less than that of providing food. Given the budget for these interventions, an additional 44,769 people could have received assistance at no additional cost had cash been provided instead of food. This suggests a significant opportunity cost in terms of reduced coverage when higher-cost transfer modalities are used. Decisions to use cash or food transfers should consider both impacts and costs.